2017
DOI: 10.1155/2017/9161083
|View full text |Cite
|
Sign up to set email alerts
|

Miniature Coplanar Implantable Antenna on Thin and Flexible Platform for Fully Wireless Intracranial Pressure Monitoring System

Abstract: Minimally invasive approach to intracranial pressure monitoring is desired for long-term diagnostics. The monitored pressure is transmitted outside the skull through an implant antenna. We present a new miniature (6 mm × 5 mm) coplanar implant antenna and its integration on a sensor platform to establish a far-field data link for the sensor readout at distances of 0.5 to 1 meter. The implant antenna was developed using full-wave electromagnetic simulator and measured in a liquid phantom mimicking the dielectri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 48 publications
(60 reference statements)
0
15
0
Order By: Relevance
“…The measured bandwidth is about 30MHz for the first band and 45MHz for the second band. The simulated radiation efficiency is about 10 percent for both bands, which is acceptable for such an ultra-miniature antenna, e.g., compare to [15,17].…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The measured bandwidth is about 30MHz for the first band and 45MHz for the second band. The simulated radiation efficiency is about 10 percent for both bands, which is acceptable for such an ultra-miniature antenna, e.g., compare to [15,17].…”
Section: Resultsmentioning
confidence: 85%
“…High demand in (ultra-)miniature antennas for IoT [15,16], medical [17], and mobile phone [18,19] applications stimulated the recent progress in antenna miniaturization. In this concern, the challenges towards decreasing the maximal size below 20 0 / λ should be mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the Archimedean spiral shape of the top plate can end up in overall size reduction. This is because the horizontal arm of the PIFA has been compacted by its spiral shape which is a quite efficient structure to attain maximum achievable bandwidth and the effective current path length [20] has increased. It has been shown that spiral structure provides lower resonance frequency and higher radiation efficiency than its meander counterpart [20].…”
Section: Antenna Designmentioning
confidence: 99%
“…However, double-sided structures (patch on one side and ground another side) are sometimes not suitable for easy mount ability on IC devices. This can be avoided with the use of single-sided co-planar structures, respectively [17].…”
Section: Introductionmentioning
confidence: 99%